On the blow up time estimation to the Schrödinger equation - Puriuškis, Gintaras (Lietuvos matematikos rinkinys, 2023)
There is considered the Schrödinger equation ∂u/∂t= i Δu+ i|u|p , u, t > 0, with initial condition u(0, x)= u0(x),  x ∈ Rn, n = 1. We prove the existence of the u0(x) such, that the blow up time estimation increases if p increases in the intervale 4 < p < p0.
Keywords: nonlinear problem; critical power; global solution; blow up; Shrodinger equation